Resilient and Responsible Smart Cities Volume 2 - Abdalla, Hassan; Rodrigues, Hugo.; Gahlot, Vimal; Salah Uddin, Mohammad; Fukuda, Tomohiro (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book aims to establish a community with attention to land use to achieve sustainable development and meet the needs of today's society. Urban planning depends on engineering, architectural, social and political pillars. It pursues this by proposing solutions, regulating environmental pollution and non-sustainable use of available resources. It showcases and even triggers further debate about connections between sustainable development, urban planning and technology in hopes of achieving sustainable development models that sustain urban expansion and shape cities that improve the overall quality of life. It views urban planning and development as vital fields that ensure the application of revolutionary approaches with new materials and processes incorporated in the most efficient manner.
Governing Sustainability in Urban Ecosystems: Arguments for a Transdisciplinary Framework -- The Dilution of Peri-Urban Socio-Cultural Identity: an Insight into Policies and Strategies in Malaysia and the European Commission -- Integrating Resilience Through Adaptability and Transformability: Ecologically Responsive Design Approach in Case of South-Western Coastal Region of Bangladesh -- The Mexico City New International Airport: A Case Study in Environmentally Sensitive Geometries -- Is Greener Commuting Possible? A Campus Case Study in Schwäbisch Hall as Contribution to Climate Protection -- Economic Feasibility of Personal Rapid Transit (PRT) Mode of Transport: A Case for Ahmedabad City, Gujarat -- eveloping Projects for Realizing of the Program "Skopje 2020 Smart Strategy" by Enhancing Citizen Approach, Engineering, Digitalization and Sensing of the City District Toward Smarter Sustainability Urban Potential in the Small Ring of Skopje -- Elderly Behavioural Ergonomic Data for Smart Cities' Design-User System -- A Novel Method of Trajectory Data Visualization to Analyze the Current Traffic Situation in Smart Cities -- Effective Participation and Sustainable Urban Development: Application of City Development Strategies Approach.
Keywords: Earth sciences; Water; Hydrology; Philosophy; Earth Sciences; Water; Philosophy; Earth Sciences